2022
DOI: 10.3390/plants11192483
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a BAHD Acyltransferase Gene Involved in Plant Growth and Secondary Metabolism in Tea Plants

Abstract: Plant acyl-CoA dominated acyltransferases (named BAHD) comprise a large appointed protein superfamily and play varied roles in plant secondary metabolism like synthesis of modified anthocyanins, flavonoids, volatile esters, etc. Tea (Camellia sinensis) is an important non-alcoholic medicinal and fragrancy plant synthesizing different secondary metabolites, including flavonoids. In the tea (C.A sinensis) cultivar Longjing 43 (LJ43), eight samples were performed into three groups for transcriptome analysis under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…Moreover, in addition to different stress-associated hormone response elements, a large number of TF binding site elements were also identified, predicting that the functional performance of tea plant BAHDs may also be regulated by different TFsas has been found in previous studies. For example, overexpression of a tea plant BAHD gene in Arabidopsis resulted in significant accumulation of anthocyanin, while many TF genes, such as WRKY, bHLH, and MYB were also significantly upregulated in the transgenic lines [ 30 ]. In addition, our correlation analysis further revealed the presence of a large number of TFs coexpressed with different BAHDs under tea geometrids or tea green leafhoppers feeding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in addition to different stress-associated hormone response elements, a large number of TF binding site elements were also identified, predicting that the functional performance of tea plant BAHDs may also be regulated by different TFsas has been found in previous studies. For example, overexpression of a tea plant BAHD gene in Arabidopsis resulted in significant accumulation of anthocyanin, while many TF genes, such as WRKY, bHLH, and MYB were also significantly upregulated in the transgenic lines [ 30 ]. In addition, our correlation analysis further revealed the presence of a large number of TFs coexpressed with different BAHDs under tea geometrids or tea green leafhoppers feeding.…”
Section: Discussionmentioning
confidence: 99%
“…However, to date, there has been little known about the BAHD family in tea plants. In a previous study, 21 BAHD members were identified from the tea plant draft genome, and ectopic overexpression analysis of one member (TEA031065) showed a dramatic increase in growth and anthocyanin content in the transgenic lines [ 30 ]. In another study, we found that the expression of the CsCHAT1 gene was upregulated several hundred-fold after tea plants were subjected to feeding by tea green leafhoppers [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…This group of specialised plant metabolites includes > 10 000 different compounds. Plant GSTFs are involved in flavonoid biosynthesis (Shao et al ., 2022; Aktar et al ., 2022). Our understanding of the functions of almost all these substances remains poor, but there is increasing evidence to suggest a role for flavonoids in plant stress resistance (Sugiyama & Yazaki, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The HCT clade belongs to a larger family of BAHD acyltransferases, involved in the specialized metabolism, including the production of phenolic compounds such as anthocyanin and suberin in roots ( Gou et al., 2009 ; Bontpart et al., 2015 ; Molina and Kosma, 2015 ). In tea ( Camellia sinensis ), overexpression of one of these BAHD genes affects not only the specialized metabolism, but also plant growth ( Aktar et al., 2022 ). How and if this HCT gene aids tomato plants in waterlogging resilience remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%